Long-term outcome of serious traumatic brain injury - Rodger Wood (European Journal of Anaesthesiology, 2008)
Follow-up studies on individuals who suffer severe head injury give a picture of poor cognitive and psychosocial outcome. However, recent evidence suggests that with the passage of time, many individuals make adjustments that compensate for early disability, leading to a reduction in social handicap with a corresponding improvement in life quality and personal satisfaction. This article will attempt to briefly review the main sources of evidence contributing to long-term outcome following serious head trauma.